The Influence of Setup Time on Job Shop Performance - Wilbrecht, Jon K.; Prescott, William B. (Management Science, 1969)
A job shop was simulated in order to determine the effect of different job priority rules involving setup times on shop performance. The seven priority rules tested were chosen on the basis that they could be implemented by job shop foremen. Assumptions in the simulation model were based on experience with an electronics company and published literature. The study indicates that, for a fully loaded shop, giving priority to be the job with the shortest actual setup time, regardless of its run time, gives the best overall performance result.